2022
DOI: 10.3390/jpm13010004
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between Wedged Hepatic Venous Pressure and Portal Pressure in Hepatic Sinusoidal Obstruction Syndrome

Abstract: Background: Wedge hepatic vein pressure (WHVP) accurately estimates the portal pressure (PP) in chronic sinusoidal portal hypertension patients. Whether this applies to patients with acute portal hypertension due to hepatic sinusoidal obstruction syndrome (HSOS) is unclear. Our aim was to assess the agreement between WHVP and PP in patients with HSOS by comparing them to decompensated cirrhosis patients. Methods: From December 2013 to December 2021, patients with pyrrolidine alkaloid-induced HSOS (PA-HSOS) rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
(39 reference statements)
0
0
0
Order By: Relevance
“…Owing to hepatic sinusoidal obstruction syndrome, it is uncertain if this tool was feasible in patients with acute portal hypertension. Cheng et al [2] aimed to assess the agreement between wedge hepatic vein pressure and portal pressure in patients with hepatic sinusoidal obstruction syndrome and with decompensated cirrhosis. They found that wedge hepatic vein pressure in patients with pyrrolidine alkaloid-induced hepatic sinusoidal obstruction syndrome did not reflect portal pressure as accurately as in patients with virus-or alcohol-related cirrhosis, primarily due to the overestimation of portal pressure.…”
mentioning
confidence: 99%
“…Owing to hepatic sinusoidal obstruction syndrome, it is uncertain if this tool was feasible in patients with acute portal hypertension. Cheng et al [2] aimed to assess the agreement between wedge hepatic vein pressure and portal pressure in patients with hepatic sinusoidal obstruction syndrome and with decompensated cirrhosis. They found that wedge hepatic vein pressure in patients with pyrrolidine alkaloid-induced hepatic sinusoidal obstruction syndrome did not reflect portal pressure as accurately as in patients with virus-or alcohol-related cirrhosis, primarily due to the overestimation of portal pressure.…”
mentioning
confidence: 99%